2020
DOI: 10.1073/pnas.2001046117
|View full text |Cite
|
Sign up to set email alerts
|

Swine acute diarrhea syndrome coronavirus replication in primary human cells reveals potential susceptibility to infection

Abstract: Zoonotic coronaviruses represent an ongoing threat, yet the myriads of circulating animal viruses complicate the identification of higher-risk isolates that threaten human health. Swine acute diarrhea syndrome coronavirus (SADS-CoV) is a newly discovered, highly pathogenic virus that likely evolved from closely related HKU2 bat coronaviruses, circulating in Rhinolophus spp. bats in China and elsewhere. As coronaviruses cause severe economic losses in the pork industry and swine are key intermediate hosts of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
116
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(118 citation statements)
references
References 87 publications
1
116
0
1
Order By: Relevance
“…Both groups originate in wildlife: rodents and horseshoe bats respectively, and are enzootic or epizootic in livestock. BetaCoV1 includes a pandemic virus that swept the human population, OC43, while SADS-CoV efficiently infects primary human respiratory and intestinal epithelial cells [22]. Our ability to anticipate threats from both groups would benefit from additional sampling, with BetaCoV1 being particularly undersampled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both groups originate in wildlife: rodents and horseshoe bats respectively, and are enzootic or epizootic in livestock. BetaCoV1 includes a pandemic virus that swept the human population, OC43, while SADS-CoV efficiently infects primary human respiratory and intestinal epithelial cells [22]. Our ability to anticipate threats from both groups would benefit from additional sampling, with BetaCoV1 being particularly undersampled.…”
Section: Discussionmentioning
confidence: 99%
“…Sampling of bats proximal to impacted farms determined that SADS-CoV outbreaks are independent spillover events of SADSr(elated)-CoVs circulating in horseshoe bats [20]. Molecular studies of SADS-CoV have identified the potential for further cross-species transmission, including the ability to infect primary human airway and intestinal cells [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these alpha-CoVs, porcine delta-CoVs (PDCoV) are prevalent in domestic pigs ( Li et al, 2018 ; Wang et al, 2019 ), but have not been surveyed in wild pigs to our knowledge. PDCoVs and SADS-CoV have been highlighted as high-risk for of a novel zoonotic spillover ( Li et al, 2018 ; Edwards et al, 2020 ). In fact, there is evidence that PDCoV has spilled over into poultry ( Boley et al, 2020 ).…”
Section: Why Might Pigs Contribute To Emergence Of Zoonotic Covs?mentioning
confidence: 99%
“…It is estimated that nearly 75% of the novel human pathogens in the last decades, the majority of which are represented by viruses, have originated in animals [1][2][3]. The pandemic of the coronavirus disease 2019 (COVID- 19) has sparked an immediate discussion regarding wildlife trade and evoked various calls to ban the activity or limit it more strictly [4]. This is due to the origin of the causative factor of COVID-19, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which is most likely to be linked primarily with a bat host, with one study demonstrating 96% identity at the whole-genome level to betacoronavirus BatCoV RaTG13 detected in Rhinolophus affinis [5].…”
Section: Introductionmentioning
confidence: 99%
“…PEDV and SADS-CoV are also emerging swine pathogens [ 17 ]. Importantly, the latter, first identified in 2016 [ 18 ], has been recently demonstrated to infect and replicate efficiently in several different primary human lung and intestinal cells, and was not neutralized by human sera [ 19 ]. All in all, this demonstrates that not only coronaviruses related to wild animals but also to livestock can display the potential risk for future emergence events in the human population.…”
Section: Introductionmentioning
confidence: 99%